Defensa de proyectos de Investigación – carrera de Educación Inicial - Llivi Ruilova, Danny Vicente (2023)
On July 20 and 21 of the current year, students of the UEB Initial Education career defended their research projects, prior to obtaining their professional title, with the presence of the MSc. María De los Ángeles Bonilla, coordinator of the race; and the members assigned to serve on the courts.